PREPARING ENGLISH AS A MEDIUM OF INSTRUCTION (EMI) LECTURERS: THE REQUIRED COMPETENCES AND RATIONALES - Yamin, Harumi Manik Ayu; Halimi, Sisilia Setiawati; Kartika, Harni Kartika (International Review of Humanities Studies, 2026)
Despite the increasing trend of English as a Medium of Instruction (EMI) in higher education in Indonesia, studies focusing on professional development for EMI lecturers remains scarce. Given the pivotal role lecturers have in the success of EMI programs, it is essential that these lecturers are provided with the necessary training and support to effectively deliver their courses in English and make well-informed pedagogical choices. This paper aims to investigate necessary sets of skills and competences required by EMI lecturers and rationales for incorporating them in EMI teacher training programs. This study employed a qualitative approach. It involved a critical review of studies to examine EMI professional development programs in various countries. The findings suggest that EMI lecturers should have various competences that include but are not limited to linguistic competence and pedagogical competence due to the complex nature of EMI programs. Suggestions to select and incorporate them in lecturer training programs are also provided in this paper.